Detection of invA gene of Salmonella from milkfish (Chanos chanos) at Sidoarjo wet fish market, Indonesia, using polymerase chain reaction technique - Sheila Marty Yanestria (Veterinary World, 2019)
Aim: The study aimed to detect the invA gene in Salmonella isolated from milkfish in the Sidoarjo wet fish market.